Analisis Penerapan Praktik Harga Transfer Dalam Penghindaran Pajak - Elia Rossa; Putri Afrilia Nurrochmah; Saefani Nur Hanifah; Salsabila Salsabila; Siska Aprilia Rahmawati; Siti Maisa Zahara; Yosi Ika Putri (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
This study analyzes the application of tax avoidance in Indonesia through transfer pricing by taking various data in the form of financial statements and other relevant information from companies listed on the Indonesia Stock Exchange (IDX) in the 2018-2020 period. This study also uses the transfer pricing methods established by the OECD to calculate fair market prices as a reference to assess the fairness of transfer prices. The results showed that most of the companies listed on the IDX practiced transfer pricing in various ways, such as setting transfer prices that are higher or lower than fair market prices, or by conducting improper transactions. The transfer pricing practices carried out by these companies are influenced by several factors, such as leverage, profitability, tunneling incentive, bonus mechanism, and tax avoidance. The practices carried out by these companies have a significant impact on taxable profit, tax expense, and state tax revenue.